Bank Bankruptcy Analysis: Capital Adequacy Ratio, Loan-to-Deposit Ratio, Non-Performing Loans, Return on Assets - Mochammad Subagio (Greenation Management and Business Review, 2026)
Bank failures in Indonesia have continued, with over a hundred banks, mostly rural banks, losing their licenses in recent years, raising concern for banking companies listed on the Indonesia Stock Exchange. Prior studies applying Altman, Springate, Zmijewski, and Grover models to Indonesian banks report inconsistent accuracy and rarely synthesize findings across periods, leaving a gap in which financial ratios most consistently explain listed-bank bankruptcy. This study examines how Capital Adequacy Ratio, Loan to Deposit Ratio, Non-Performing Loan, and Return on Assets relate to bank bankruptcy in Indonesia. A qualitative descriptive approach using a systematic literature review was applied, drawing on fifty secondary sources published between 2021 and 2026 from Springer, Wiley, ProQuest, Emerald, Taylor and Francis, Sage, Sinta, Copernicus, and Google Scholar. The review finds that all four ratios influence bank bankruptcy, with weak capital, aggressive lending, deteriorating credit quality, and declining profitability jointly signaling elevated risk. The novelty lies in integrating these ratios into one conceptual model built from multi-year literature synthesis rather than a single-period dataset, offering stakeholders and regulators a consolidated early-warning reference